2010
DOI: 10.1089/gtmb.2009.0039
|View full text |Cite
|
Sign up to set email alerts
|

Association of PAI-1 4G/5G and -844G/A Gene Polymorphisms and Changes in PAI-1/Tissue Plasminogen Activator Levels in Myocardial Infarction: A Case–Control Study

Abstract: This study indicated that the risk of MI was notably high in 4G and -844A carriers with elevated plasma PAI-1 and were associated with reduced tPA levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 24 publications
2
31
1
3
Order By: Relevance
“…Polymorphisms which have been presented below may be the cause of inherited thrombophilia and may result in pregnancy loss. The hypothesis is based on a number of cardiology studies which have confirmed the involvement of these polymorphisms in thrombotic incidents [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphisms which have been presented below may be the cause of inherited thrombophilia and may result in pregnancy loss. The hypothesis is based on a number of cardiology studies which have confirmed the involvement of these polymorphisms in thrombotic incidents [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, Isordia-Salas I et al found that the 4G allele is an independent risk factor for acute MI in young patients, similar to smoking, hypertension, and a family history of inherited cardiovascular disease in Mexico [5]. In 2010, Abboud N et al found that the MI risk is notably high in 4 G carriers with elevated plasma PAI-1 in a Tunisian population [6]. However, in 2011, Rallidis LS et al found that the 4 G allele of PAI-1 4G/5G polymorphism is less frequent among very young survivors of MI compared with that in matched controls in Greece [7].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the meta analysis results suggest that it was the 5G/5G genotype, and not 4G/4G, that was associated with an increased stroke risk, although its carriers decreased the plasma PAI 1 levels [9]. On the other hand, the 4G/4G genotype has been clearly associated with increased myocardial infarction risks [9,27]. There are also other possible explanations of this contradiction.…”
Section: Discussionmentioning
confidence: 98%
“…As a result, the thrombolytic activity is downregulated, and the risk of thrombus formation grows. Several studies have shown that 4G/4G homozygotes by the -675 4G/5G polymorphisms have an increased risk of thrombosis and myocardial infarction [25][26][27]. It is also known that the plasma levels of PAI 1 grow significantly in the course of a stroke, leading to the depletion of the patient's fibrin olytic system [1].…”
Section: Discussionmentioning
confidence: 99%